Evaluation on Delineation Methods for Ion-adsorption Type Rare Earth Ore Body - DENG Mao-chun; WANG Deng-hong; ZENG Zai-lin; ZHANG Yong-zhong; ZHAO Zhi; ZOU Xin-yong; CHEN Bin-feng (Yankuang ceshi, 2013)
Ion-adsorption type rare earth ore is unique and a valuable resource in China. Total rare earth oxides (SREO) and leaching quantities of rare earth oxides (SREO) are important indices of evaluation of the scope and value of rare earth resources. For forty years however, the exploration evaluation method for this kind of deposit has been delineated according to the total amount, and quantified by rare earth composition, at odds with the current mining technology and the current value of rare earth elements. In this paper, comparative studies in three methods for ore body delineation (TREO, SREO, and single element) are described, based on the practice of mineral exploration, results of systematic samples test and indices of ore body delineation by SREO and single element according to the rare earth prices of the last five years. The results showed that the areas and thickness of ore body and resources reserves delineated by SREO (≥0.03%) are significantly greater than ore body delineated by TREO (≥0.05%) in the same area. There are some areas or parts which are not mined by the total index, but by the leaching ore quantity index, while there are other areas or parts which are mined by the total index but not by the leaching quantity index. Ore body delineated by single rare earth element oxides, which can intuitively reflect the major component and distribution of a rare earth ore, is beneficial to embody the economic value of the single rare earth deposit. Compared to the methods of ore body delineation with TREO and SREO, the method for ore body delineated by single rare earth is more careful, reasonable, and worth further study. However, the misnomer that some element content is too low to separate from the ore body may also emerge, and lead to the loss of resources therefore, it is important to strengthen the comprehensive evaluation for ion-adsorption type rare earth ore body delineation.